Development and evaluation of 4-(pyrrolidin-3-yl)benzonitrile derivatives as inhibitors of lysine specific demethylase 1. Issue 20 (15th October 2017) - Mould, Daniel P.; Bremberg, Ulf; Jordan, Allan M.; Geitmann, Matthis; McGonagle, Alison E.; Somervaille, Tim C.P.; Spencer, Gary J.; Ogilvie, Donald J.
Graphical abstract: Abstract: As part of our ongoing efforts to develop reversible inhibitors of LSD1, we identified a series of 4-(pyrrolidin-3-yl)benzonitrile derivatives that act as successful scaffold-hops of the literature inhibitor GSK-690. The most active compound, 21g, demonstrated a K d value of 22 nM and a biochemical IC50 of 57 nM. In addition, this compound displayed improved selectivity over the hERG ion channel compared to GSK-690, and no activity against the related enzymes MAO-A and B. In human THP-1 acute myeloid leukaemia cells, 21g was found to increase the expression of the surrogate cellular biomarker CD86. This work further demonstrates the versatility of scaffold-hopping as a method to develop structurally diverse, potent inhibitors of LSD1.